Taguchi optimization of bevel angle in plasma jet cutting process of aluminium alloy 5083 - Peko, Ivan; Nedić, Bogdan; Dunđer, Marko; Samardžić, Ivan (Journal of Production Engineering, 2020)
This paper focuses on Taguchi optimization of the bevel angle in the plasma jet cutting process of aluminum alloy EN AW 5083. Experimental work for this paper was conducted using a standard L27 Taguchi’s orthogonal array design, where three plasma jet cutting parameters, namely cutting speed, arc current, and cutting height, were each set at three different levels. Through the analysis of means, analysis of variance, and two-way interaction plots, significant plasma jet cutting process parameters and the optimal combination of their levels for achieving minimal bevel angle were identified. The results indicate that all three process parameters have a significant impact on the bevel angle response. The predicted response under optimal plasma jet cutting conditions closely matches the observed experimental results for bevel angle.